2017
DOI: 10.1155/2017/3489617
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia, Pain, Muscle Functions, and Functional Performances among Older Persons with Low Back Pain

Abstract: Objectives This study aims (1) to determine the association between kinesiophobia and pain, muscle functions, and functional performances and (2) to determine whether kinesiophobia predicts pain, muscle functions, and functional performance among older persons with low back pain (LBP). Methods This is a correlational study, involving 63 institutionalized older persons (age = 70.98 ± 7.90 years) diagnosed with LBP. Anthropometric characteristics (BMI) and functional performances (lower limb function, balance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 69 publications
(84 reference statements)
1
42
0
8
Order By: Relevance
“…Some evidence support the ideas that kinesiophobia could interfere with physical capacity measurements [16,21,22] and that professional exercise supervision and kinesiophobia management might have a positive effect in exercise adherence in chronic pain conditions [23]. The present case participant led us to hypothesize that this could also be the case in older cancer patients.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Some evidence support the ideas that kinesiophobia could interfere with physical capacity measurements [16,21,22] and that professional exercise supervision and kinesiophobia management might have a positive effect in exercise adherence in chronic pain conditions [23]. The present case participant led us to hypothesize that this could also be the case in older cancer patients.…”
Section: Discussionsupporting
confidence: 71%
“…Associations have been found between kinesiophobia measured with the Tampa scale and physical capacity tests assessing gait speed and dynamic balance. In older women with chronic musculoskeletal pain, an association was found between the Tampa scale score and the result for the Timed up-and-go test (almost identical to the 8FUG test) [16,21].…”
Section: Trials and Clinical Practicementioning
confidence: 89%
“…Ishak, et al concluded that kinesiophobia predicted mobility and balance in older persons with low back pain. Kinesiophobia should be continuously assessed in clinical settings to recognize the obstacles that may affect patient's compliance towards a rehabilitation program in low back pain [30]. Osumi, et al also found evidence of a particular lumbar movement pattern associated with kinesiophobia.…”
Section: Resultsmentioning
confidence: 99%
“…They fear to induce pain by moving and develop fear avoidance behavior (kinesiophobia). Hence these patients are caught in a vicious circle: Movement avoidance leads to loss of muscular abilities, that in turn favors pain, and pain again leads to the avoidance of physical activity [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%